1983
DOI: 10.1007/bf00691982
|View full text |Cite
|
Sign up to set email alerts
|

Tactile-like corpuscles in neurofibromas: Immunohistochemical demonstration of S-100 protein

Abstract: Tactile-like corpuscles in neurofibroma tissues were examined by the indirect immunoperoxidase method using rabbit anti-S-100 sera. In all five cases examined, positive staining was observed in their constituent cells, both in the flattened cytoplasm and nuclei. On examination of the normal peripheral nervous system, positive staining was exclusively confined to Schwann cells in the nerve bundles and Schwann-related cells such as lamellar cells in the Meissner corpuscle, whereas staining was negative in perine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 11 publications
3
10
0
Order By: Relevance
“…Our results are consistent with focal, well developed schwannian differentiation arising in a more undifferentiated cellular background. Meissnerian and Pacinian differentiation have been well documented previously in neurofibromas, and in at least one instance the Meissnerian corpuscles expressed S100 protein, supporting their Schwann cell origin 20 . Documentation of somatic loss of heterozygosity and mutation of the NF1 gene in NF1-associated neurofibromas 21,22 also suggests origin from a single cell type.…”
Section: Discussionsupporting
confidence: 66%
“…Our results are consistent with focal, well developed schwannian differentiation arising in a more undifferentiated cellular background. Meissnerian and Pacinian differentiation have been well documented previously in neurofibromas, and in at least one instance the Meissnerian corpuscles expressed S100 protein, supporting their Schwann cell origin 20 . Documentation of somatic loss of heterozygosity and mutation of the NF1 gene in NF1-associated neurofibromas 21,22 also suggests origin from a single cell type.…”
Section: Discussionsupporting
confidence: 66%
“…Along with morphologic observations, this immunohistochemical staining pattern supports that these corpuscle-like structures found incidentally in our case, are similar to the tactile corpuscle-like structures described in peripheral nerve sheath tumors or dermal nevi and are of Schwann-related cell origin [4]. In fact, several other authors have come to the conclusion that these structures are composed predominantly of Schwann cells [3]. …”
Section: Discussionsupporting
confidence: 90%
“…The presence of such structures in plexiform neurofibromas has been associated with von Recklinghausen's disease [6]. The cells comprising these structures are arranged in a whorled or lamellated arrangement and are considered to be of perineural and schwannian nature [3,4]. …”
Section: Introductionmentioning
confidence: 99%
“…15 Although the differentiation of TCLBs has been debated in the past, 5,10 they show Schwann cell differentiation. 3,11 Nonsyndromic TCLBs have been described only rarely in the GI tract-type mucosa. The initial description was by Wills et al, 8 who reported an incidental colonic In the present study, we analyzed a series of 9 TCLB cases identified as incidental findings.…”
Section: Discussionmentioning
confidence: 99%